Effects of Leymus chinensis hay and alfalfa hay on growth performance, rumen microbiota, and untargeted metabolomics of meat in lambs - Wang, Hanning; Meng, Lingbo; Mi, Lan (Frontiers in Veterinary Science, 2023)
Objective The objective of this study was to compare the effects of Leymus chinensis hay and alfalfa hay as the roughage on the rumen bacterial and the meat metabolomics in lambs. Methods Fourteen male lambs were randomly assigned to two dietary treatments (one was fed with concentrate and Leymus chinensis hay; another was fed with concentrate and alfalfa hay) with seven replicates per treatment. The feeding experiment lasted for 60 days. Lambs were slaughtered at the end of the feeding experiment. Growth performance, carcass performance and weights of various viscera were determined. The longissimus dorsi and rumen contents were collected for untargeted metabolomics and 16S rDNA amplicon sequencing analysis, respectively. RESULTS The lambs fed with alfalfa hay showed significantly increased in average daily gain, carcass weight, dressing percentage, loin-eye area and kidney weight as well. Feeding Leymus chinensis hay and alfalfa hay diets resulted in different meat metabolite deposition and rumen bacterial communities in lambs. The relative abundance of phyla Fibrobacteres, Bacteroidetes, and Spirochaetes were greater in the Leymus Chinensis hay group, while, the relative abundance of Firmicutes, Proteobacteria, Fusobacteria, and Verrucomicrobia were greater in the alfalfa hay group. Based on untargeted metabolomics, the main altered metabolic pathways included alanine, aspartate and glutamate metabolism, D-glutamine and D-glutamate metabolism, phenylalanine metabolism, nitrogen metabolism, and tyrosine metabolism. Several bacteria genera including BF31, Alistipes, Faecalibacterium, Eggerthella and Anaeroplasma were significantly correlated with growth performance and meat metabolites. CONCLUSION Alfalfa hay improved growth performance and carcass characteristics in lambs. Leymus chinensis hay and alfalfa hay caused different meat metabolite deposition through modifying the rumen bacterial community. These findings will be beneficial to the future forage utilization for sheep growth and carcass performance and meat quality improvement.